Combined Optical-Electrical Optimization of Cd1−xZnxTe/Silicon Tandem Solar Cells - Giray Kartopu (Materials, 2020)
Although the fundamental limits have been established for the single junction solar cells, tandem configurations are one of the promising approaches to surpass these limits. One of the candidates for the top cell absorber is CdTe, as the CdTe photovoltaic technology has significant advantages: stability, high performance, and relatively inexpensive. In addition, it is possible to tune the CdTe bandgap by introducing, for example, Zn into the composition, forming Cd1−xZnxTe alloys, which can fulfill the Shockley–Queisser limit design criteria for tandem devices. The interdigitated back contact (IBC) silicon solar cells presented record high efficiencies recently, making them an attractive candidate for the rear cell. In this work, we present a combined optical and electrical optimization of Cd1−xZnxTe/IBC Si tandem configurations. Optical and electrical loss mechanisms are addressed, and individual layers are optimized. Alternative electron transport layers and transparent conductive electrodes are discussed for maximizing the top cell and tandem efficiency.